Proteomics Technologies and Applications - Abdurakhmonov, Ibrokhim Y. (IntechOpen, 2019)
Proteomics Technologies and Applications reviews and describes the nature and application of molecules with proteins or peptides, and elucidates and predicts the possible molecular and physiological causes related to changing proteomic profiles. Chapters target various methods and tools available for analysis, detection, separation, quantification, and localization of cell proteomes of a biological system, which are helpful as biomarkers for various disease prognoses and diagnoses.